Proceedings of the 2006 Conference on Applications, Technologies, Architectures, and Protocols for Computer Communications 2006
DOI: 10.1145/1159913.1159962
|View full text |Cite
|
Sign up to set email alerts
|

Drafting behind Akamai (travelocity-based detouring)

Abstract: To enhance web browsing experiences, content distribution networks (CDNs) move web content "closer" to clients by caching copies of web objects on thousands of servers worldwide. Additionally, to minimize client download times, such systems perform extensive network and server measurements, and use them to redirect clients to different servers over short time scales. In this paper, we explore techniques for inferring and exploiting network measurements performed by the largest CDN, Akamai; our objective is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 20 publications
3
66
0
Order By: Relevance
“…To drive CRP, we employ the Akamai CDN [1] and gather CDN redirections using Yahoo 1 and Fox News 2 . As reported in [42], lookups to these names result in redirections that reflect dynamic network conditions. During each evaluation period, we determine CDN-based relative positions by issuing recursive DNS queries to reveal the mapping of hosts to replica servers.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…To drive CRP, we employ the Akamai CDN [1] and gather CDN redirections using Yahoo 1 and Fox News 2 . As reported in [42], lookups to these names result in redirections that reflect dynamic network conditions. During each evaluation period, we determine CDN-based relative positions by issuing recursive DNS queries to reveal the mapping of hosts to replica servers.…”
Section: Discussionmentioning
confidence: 92%
“…Based on a study of CDN redirection from two different CDN providers, Johnson et al [16] argue that these CDNs commonly avoid bad recommendations rather than select optimal servers. More recently, through a detailed measurement of the Akamai CDN, we show that CDN redirections are primarily driven by network conditions, specifically network latencies on the paths between clients and the Akamai servers, and are updated frequently enough as to be useful for control [42]. Our early study illustrated the potential benefits of employing CDN redirections for identifying good detouring paths and demonstrated that in approximately 50% of scenarios, the best measured one-hop path through an Akamai server outperforms the direct path in term of latency.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that the use of an additional selection component such as an Akamai-server is more bene¿cial than IP routing in more than 50% of the scenarios [22]. Therefore, our work uses a similar forwarding scheme to the ICN framework Content Centric Network / Named Data Networking (CCN/NDN) [4]; each router forwards a request to the next router based on the requested service name.…”
Section: Related Workmentioning
confidence: 99%
“…Fig. 1 provides a detailed example of an Akamai DNS translation, which is explained in depth in [1]. In summary, the Akamai infrastructure returns the IP addresses of two Akamai edge servers that it expects to offer high performance to the Web client.…”
Section: A Dns Translationmentioning
confidence: 99%